Influence of Plant Oils and Containers on Seed Storability of Alllium Cepa L. - LOKESH; SS JAKHAR; SUNIL KUMAR; BITTU RAM (Seed Research, 2026)
An experiment was conducted to investigate the influence of plant oils and packaging materials on the longevity of onion seed (variety: Hisar Onion-4). The seeds were coated with eight plant oils seed and were kept in two containers viz., Cloth bag and Plastic zipling bag up to nine months under ambient conditions in Seed Pathology laboratory of Department of Seed Science & Technology, CCSHAU, Hisar. The samples were drawn at three month intervals for ascertaining the seed quality parameters. The seeds coated with neem oil (5 ml kg-1 seed) and stored in plastic zipling bag were found better for the maintenance of higher seed quality parameters [germination (66.33%), root length (3.27cm), shoot length (5.47cm), mean seedling dry weight (26.7mg), vigour indices1 & II (579.4 & 1912), electrical conductivity (0.483 µS/cm/seed), mycoflora (0.643%), emergence index (6.33) and seedling establishment (54.17%)] during study period. The study suggested that the use of appropriate packaging material and seed treatment could be useful to prolong the storage life and seed health of onion seeds.